فعالية قنوات انتقال أثار السياسة النقدية في الجزائر (Q1 2002- Q4 2021) : The effectiveness of monetary policy transmission channels in Algeria (2002:Q1-2021:Q4) - عميروش شلغوم; مريم بلعزوز (Journal of North African Economies, 2025)
This paper aims to study the effectiveness of monetary policy channels in Algeria over the period 2002:Q1–2021:Q4. We use a Vector Autoregressive Model (VAR). The empirical results show the ineffectiveness of monetary transmission channels. Consequently, the monetary shocks, through discount rate, required reserve, and liquidity absorption by deposit auction and marginal deposit facility, does not have a significant effect on inflation and real non-hydrocarbon output. Many factors such as real sector constraints, bank excess liquidity, limited international financial market integration, limited financial sector development, all contribute to weaken the monetary transmission in Algeria.